2010
DOI: 10.1007/s00428-010-0943-3
|View full text |Cite
|
Sign up to set email alerts
|

Reciprocal correlation between the expression of cyclooxygenase-2 and E-cadherin in human bladder transitional cell carcinomas

Abstract: Carcinoma cells become more motile and invasive via downmodulation of E-cadherin. Cyclooxygenase-2 (COX-2) expression is associated with tumor invasion and metastasis. The aim of this study is to investigate the relationship between the expression of COX-2 and E-cadherin in a bladder cancer cell line and human bladder transitional cell carcinoma (TCCs). Phorbol 12-myristate 13-acetate (PMA) treatment for 5637 bladder cancer cells increased COX-2 expression, slightly induced Slug expression, and decreased E-cad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
19
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 32 publications
5
19
0
Order By: Relevance
“…Similar results were obtained by Jang et al (2010), who found that the expression of E-cadherin decreases in case of HG tumors.…”
Section: Disscussionsupporting
confidence: 89%
“…Similar results were obtained by Jang et al (2010), who found that the expression of E-cadherin decreases in case of HG tumors.…”
Section: Disscussionsupporting
confidence: 89%
“…Thus, Celecoxib was found to be effective in upregulating E-cadherin thus reversing the EMT in cell lines derived from head and neck squamous cancer, colon cancer, gastric cancer and breast cancer [101][102][103][104]. Another COX-2 inhibitor, Etodolac, had a similar effect in bladder cancer cell lines, where EMT reversal was also seen in vivo in xenografts of the human bladder cancer cell line T24 [105].…”
Section: Cox-2 Is Associated With Breast Cancer Invasion Via Emtmentioning
confidence: 67%
“…COX-2 expression was significantly higher in SCC than in precursors and NS (p < 0.05). An inverse correlation was found between the expression of COX-2 and E-cadherin in a variety of tumors [18,29]. We found COX-2 expression in 68 % (13 out of 19) of SCC with focal loss of E-cadherin and in 22 % (6 out of 22) of SCC with normal expression of E-cadherin (p00.008).…”
Section: Resultsmentioning
confidence: 61%
“…Induction of PGE 2 represses E-cadherin expression through the induction of Snail and ZEB1 in non-small cell lung cancer and colon cancer [18,33,34]. Ectopic expression of COX-2 in or PGE 2 treatment of bladder cancer cells reduces E-cadherin expression [29]. Recently it was found that E-cadherin expression is inhibited via the PGE 2 -EP2 signaling pathway during ultraviolet-induced cutaneous squamous cell carcinoma progression [17].…”
Section: Discussionmentioning
confidence: 97%